2007
DOI: 10.1111/j.1365-2265.2007.02925.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human luteinizing hormone, lutropin alfa, for the induction of follicular development and pregnancy in profoundly gonadotrophin‐deficient women

Abstract: Coadministration of lutropin alfa 75 IU and follitropin alfa is safe and effective in inducing follicular development and pregnancy in hypogonadotrophic hypogonadal women with profound gonadotrophin deficiency in a setting consistent with established medical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
0
29
0
1
Order By: Relevance
“…Our data support the theory that there is an LH threshold below which adverse effects are seen in human assisted reproduction. Studies on patients with hypothalamic amenorrhea have shown the addition of LH is necessary to achieve appropriate follicular and endometrial development (20)(21)(22)(23)(24)(25). However, it has also been shown that many normogonadotropic patients can be stimulated successfully with FSH alone in both GnRH antagonist and GnRH agonist cycles (26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the theory that there is an LH threshold below which adverse effects are seen in human assisted reproduction. Studies on patients with hypothalamic amenorrhea have shown the addition of LH is necessary to achieve appropriate follicular and endometrial development (20)(21)(22)(23)(24)(25). However, it has also been shown that many normogonadotropic patients can be stimulated successfully with FSH alone in both GnRH antagonist and GnRH agonist cycles (26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…225 One caveat is that most women with CHH do not secrete endogenous LH and, thus, require a complement of LH to stimulate local production of androgen substrates by theca cells, which facilitates sufficient secretion of estradiol by the dominant follicle. [226][227][228] Physiologic estradiol secretion promotes optimal endometrial development and the cervical mucus production needed for sperm transit and embryo implantation. 229 Typically, subcutaneous FSH doses of 75-150 IU per day are sufficient.…”
Section: Induction Of Female Sexual Characteristicsmentioning
confidence: 99%
“…Stimulation studies with highly purified or recombinant FSH showed a clear correlation between remaining LH levels and stimulation outcome in HH women 1,53,70,103. Below a LH level of 1 U/L, FSH alone was not capable of stimulating follicular growth 104.…”
Section: Gonadotropic Treatment In Hh Womenmentioning
confidence: 97%
“…The low or undetectable gonadotropins portray the common endpoint of different diseases and circumstances. Despite a few cases of pituitary origin such as adenomas or inflammation (hypophysitis), the majority of HH patients suffer from a disturbed hypothalamic gonadotropin-releasing hormone (GnRH) secretion 1,2. The irregular GnRH secretion can be traced back to a morphological correlate such as Kallmann’s syndrome, adrenal hypoplasia congenita (in men), GnRH gene mutation or Leptin gene mutation in just 10% of all cases 3,4.…”
Section: Introductionmentioning
confidence: 99%